Decomposing productivity growth in Malaysian food manufacturing industry - Mohamad, N.; Said, F. (Academic Journals, 2010)
In this study, a mathematical programming-based optimization technique known as data envelopment analysis, DEA is used to compute and analyze the decomposition of Malmquist index of total factor productivity, TFP into technological change, technical efficiency change and scale efficiency change by utilizing an output-oriented DEA model under the assumptions of constant and variable returns to scale. The methodology is applied to selected 5-digit Malaysian food manufacturing sub-industries using annual time-series data for the period 2002 to 2007. The results suggest that the TFP growth is largely due to positive technological change or frontier shift rather than technical efficiency change.